Sales force management - Churchill, Gilbert A. (New York Irwin Professional Publishing, 1997)
This research/theory based text cites the theoretical foundations of sales mangement. The material in previous editions has been expanded to include empowerment, stress management, leadership and strategic management. Experimental applications are also included appearing at the end of the chapters, providing the student with the opportunity to work relevant topics.
Keywords: management -- sales management